CARICOM's selected economic indicators 1985, 1995-1999 : a statistical profile of the CARICOM Single Market and Economy (CARICOM Secretariat GeorgetownGY, 2001)
Presents a core set of economic indicators of CARICOM Member States.
Keywords: ECONOMIC INDICATORS